Penetration into Cancer Cells via Clathrin-Dependent Mechanism Allows L-Asparaginase from Rhodospirillum rubrum to Inhibit Telomerase - Anna A. Plyasova; Marina V. Pokrovskaya; Olga M. Lisitsyna; Vadim S. Pokrovsky; Svetlana S. Alexandrova; Abdullah Hilal; Nikolay N. Sokolov; Dmitry D. Zhdanov (MDPI AG, 2020)
The anticancer effect of L-asparaginases (L-ASNases) is attributable to their ability to hydrolyze L-asparagine in the bloodstream and cancer cell microenvironment. Rhodospirillum rubrum (RrA) has dual mechanism of action and plays a role in the suppression of telomerase activity. The aim of this work was to investigate the possible mechanism of RrA penetration into human cancer cells. Labeling of widely used L-ASNases by fluorescein isothiocyanate followed by flow cytometry and fluorescent microscopy demonstrated that only RrA can interact with cell membranes. The screening of inhibitors of receptor-mediated endocytosis demonstrated the involvement of clathrin receptors in RrA penetration into cells. Confocal microscopy confirmed the cytoplasmic and nuclear localization of RrA in human breast cancer SKBR3 cells. Two predicted nuclear localization motifs allow RrA to penetrate into the cell nucleus and inhibit telomerase. Chromatin relaxation promoted by different agents can increase the ability of RrA to suppress the expression of telomerase main catalytic subunit. Our study demonstrated for the first time the ability of RrA to penetrate into human cancer cells and the involvement of clathrin receptors in this process.